COMPARATIVE ANALYSIS OF QUANTITATIVE COMPUTED TOMOGRAPHY DATA AND HISTOLOGICAL FINDINGS IN PATIENTS WITH GIANT CELL BONE TUMOR TREATED WITH DENOSUMAB - S. A. Tabakaev; I. G. Frolova; I. I. Anisenya; N. V. Vasilyev; A. V. Bogoutdinova; P. K. Sitnikov (Сибирский онкологический журнал)
Background. Giant cell tumor of bone (GCTB) is a common benign lesion accounting for 4–9.5 % of all primary bone tumors. Although surgery is considered the method of choice in the treatment of GCT, however, denosumab, a genetically engineered drug with a novel mechanism of  action, has been recently used to treat GCTB. Histological examination of a surgical specimen is undoubtedly the most objective method for assessing the effectiveness of the treatment. However, in some cases it is necessary to assess the effectiveness of conservative therapy at the stages of its implementation.The purpose of the study was to compare CT-densitometry findings with histological findings in GCTB patients treated with denosumab.Material and Methods. The study included 30 patients aged from 28 to 59 years with histologically verified GCTB, who received targeted therapy with denosumab followed by surgery. The changes in tumor structure during denosumab therapy and surgical specimens of the tumor were assessed. Results. The relationship between the CT-densitometry findings and histopathological findings of surgical specimens was revealed in GCTB patients treated with denosumab. Conclusion. CT-densitometry findings were shown can be used topredict pathological response of the tumor to denosumab treatment.